Diversifikasi Pangan Olahan Jagung Menjadi Sirup Untuk Meningkatkan UMKM di Desa Sindangratu - Rahmawati, Dewi; Rasyid, Ervin Abdal; Rijky, Dimas; Nuriawan, Ridzky Guntur; Mujahidin, Bangkit; Rusyanto, Prayoga Pangestu; Alrahmat, Piki; Alfiyah, Bintang Nur; Syafaat, Anisa Syifa; Fadilah, Eva Nurul; Fahmi, Muhammad Zaki; Akhyar, Taufiq Daniel; Fahrulloh, Trinjani; Muttaqien, Abdullah Harits; Fitriansyah, Elsa Hildiani; Lisnawati, Ayuni; Nisa, Neng; Putri, Marsela; Nurhalifah, Elsa; Fallah, Doni; Ergiyansyah, Suryana (Institut Teknologi Garut, 2022)
Corn is one type of agro-industry which is a potential superior in Sindangratu Village, Wanaraja, Garut. Corn is a plant with high nutritional content and has economic value, thus corn can be an agribusiness that has added value if it is increased into several types of processed food. But there are still many corn farmers who have not been able to process corn into its derivative products, corn is usually only sold raw to the market. The purpose of carrying out this community service activity is to produce processed corn products, one of which is corn syrup and see the opportunities for corn syrup if it is produced, thereby increasing the income of corn farmers in Sindangratu Village. The analytical method used is to analyze technical and production aspects, business feasibility by calculating the cost of production, marketing aspects, and community support. Business feasibility is seen based on the profit that will be obtained in one month for making 864 bottles of corn syrup, namely Rp. 1,688,409 with a selling price of Rp. 8,061 per bottle (150 ml).